Discipline and flexibility: a behavioural perspective on microfinance product design. (3rd July 2017) - Labie, Marc; Laureti, Carolina; Szafarz, Ariane
Abstract: The success of both microcredit and micro-savings products rests upon simplicity and standardization in order to stimulate client discipline. However, these products lack flexibility. This paper attempts to make sense of behavioural product design in microfinance. We focus on the potential trade-offs between discipline and flexibility. While discipline devices encourage clients to make payments on time, microfinance product flexibility improves clients' day-to-day money management and helps them cope with shocks. Our contribution is twofold. Firstly, we highlight the evidence-based advantages and disadvantages of flexible products in microfinance. Secondly, we present best-practice examples of flexible products offered by microfinance institutions worldwide.